(3GSJbdGd GdSdWI GdbVGFjI (B: s (3OQGSI ebGQfI ai GdbGfhfjf GdeUQi hGdchjJi (B/ s - (3WdGd NGdO eQRhb GdQTjOis; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2011)
(3JJfGhd gPg GdQSGdI ehVhYG ef Cge GdehVhYGJ GdJi TZdJ h eGRGdJ JTZd GgJeGeGJ GdEfSGf Ydi eQ GdYUhQ CdG h gh ehVhY (B- (3JMbjb GdYOGdI (B- (3h EQSGA bhGYOgG Ydi GdCQV h Pdc ef NdGd GSJbdGd hMjOI h fRGgI GdLgGR GdbGFe Ydi eQab GdYOGdI h gj GdSdWI GdbVGFjI(B. (3aHOhf GdSdWI GdbVGFjI dG jhLO YOd aj GdeLJeY Ch GdOhdI Ydi MO ShGA h dG jTYQ GdCaQGO HGdCef Ch GdCeGf ShGA HGdfSHI dMeGjI Mbhbge Ch Uhf MQeGJge(B: (3h GdYOd CSGS Gdedc(B: (3ceG Jbhd GdebhdI GdTgjQI(B: (3h gh GdejRGf GdPj jYjO GdCehQ Edi fUGHgG h jQOY GdNGQL Ydi GdbGfhf h jYjOg Edi QTOg h UhGHgs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2011.s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: 645- 680 (3UaMIs
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3eQJHGJ GdbVGIs; (3GdSdWI GdbVGFjIs; (3GdbGfhf GdchjJjs; (3GdaUd Hjf GdSdWGJs; (3GSJbdGd GdbVGAs; (3MUGfI GdbVGIs; (3MjGO GdbGVis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes